A new species of Phyllomedusa (Anura: Hylidae: Phyllomedusinae) from northwestern Venezuela - Barrio-Amorós, César L. (Zootaxa, 2006)
A new species of the Phyllomedusa tarsius group (Anura: Hylidae: Phyllomedusinae) from northwestern Venezuela can be differentiated from other species in the group by its small size, white and pink bars on the concealed surfaces of legs, and distinctive mating call; it is known only from xeric areas in the vicinity of Serranía de San Luis, Estado Falcón, Venezuela. The call is described, and some natural history data is also provided. The Phyllomedusa tarsius group includes five species and is defined by morphological characters (with one putative synapomorphy).